EVALUASI SIFAT KUANTITATIF BEBERAPA KULTIVAR UBIJALAR LOKAL YANG TAHAN TERHADAP Elsinoe batatas - Niluh Suryaningsih (Universitas Musamus, Merauke, Papua, 2011)
This study aims to get the best production of tubers produced by some sweet potato cultivars grown in natural environmental conditions. The research was conducted in Manokwari using 32 sweet potato cultivars, 30 among of them is local cultivars from various locations, a national cultivars is only Prambanan and one from another is introduction cultivar (SQ). The main limiting factor that is created from this research is the attack of scab disease (Elsinoe batatas), and witches' broom disease. However, the results showed that in some local cultivars from Papua did not show any attack of scab disease (Elsinoe batatas). Another limiting factor is the growing environment of plants. Most of the research materials which from the highlands, then even if not attacked by scab disease (Elsinoe batatas) is also did not show the results of the tubers